2020
DOI: 10.5005/jp-journals-10001-1406
|View full text |Cite
|
Sign up to set email alerts
|

Management of Retrosternal Goiter without Sternotomy: A Retrospective Review in a Tertiary Care Center

Abstract: Background and aims: Retrosternal goiter (RG) is defined as a thyroid mass of which more than 50% is located below the thoracic inlet. It can give rise to various compression symptoms like dyspnea and dysphagia, which necessitate the need for surgery. The aim of this study is to review the management of patients with retrosternal extension of goiter through a neck collar incision without sternotomy with minimal morbidity at a tertiary care center. Materials and methods: A retrospective analysis of 224 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Regarding the demographics, the incidence of male: female was 1:4.25 with mean age of 57.1 years, which is like that published by Veerabhadraiah and his colleagues where the male: female ratio was 1:4.25 with mean age of 51 years while others like Varshney reported male: female incidence of 1:2.6 but the mean age was of 52 years (1,15) . Khairy et al (2) reported mean age of 54 years and the incidence of females was 3.3 times males.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding the demographics, the incidence of male: female was 1:4.25 with mean age of 57.1 years, which is like that published by Veerabhadraiah and his colleagues where the male: female ratio was 1:4.25 with mean age of 51 years while others like Varshney reported male: female incidence of 1:2.6 but the mean age was of 52 years (1,15) . Khairy et al (2) reported mean age of 54 years and the incidence of females was 3.3 times males.…”
Section: Discussionsupporting
confidence: 76%
“…RSG is reported in the literature to range from 3 to 20% of the patients undergoing thyroidectomy operation. This wide range in the incidence is mostly due to the different definitions given for RSG (1,15) . In our study we included only the cases with goiters extending deep in the mediastinum with more than of 50% of its main portion in the retrosternal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation